Knowledge and beliefs about vaccination in pregnant women before and during the COVID-19 pandemic - Bruno, Stefania; Nachira, Lorenza; Villani, Leonardo; Beccia, Viria; Di Pilla, Andrea; Pascucci, Domenico; Quaranta, Gianluigi; Carducci, Brigida; Spadea, Antonietta; Damiani, Gianfranco; Lanzone, Antonio; Federico, Bruno; et al. (Frontiers in Public Health, 2022)
Introduction Vaccine hesitancy threatens the health of populations and challenges Public Health professionals. Strategies to reduce it aim to improve people's risk perception about vaccine-preventable diseases, fill knowledge gaps about vaccines and increase trust in healthcare providers. During pregnancy, educational interventions can provide a proper knowledge about safety and efficacy of maternal and childhood vaccinations. Fighting hesitancy and clarifying doubts is fundamental during the COVID-19 pandemic, which may have affected people's knowledge and beliefs toward vaccination. This study aimed at assessing if the advent of the pandemic was associated with changes in pregnant women's knowledge and beliefs toward vaccination, and trust in healthcare services. Methods A repeated cross-sectional study was conducted through self-reported questionnaires in a Roman teaching hospital, where educational classes about vaccinations are routinely held as part of a birthing preparation course. Data were collected on a sample of pregnant women before and during the pandemic. Free-of-charge flu vaccinations were offered to all course participants and adherence to flu vaccination was assessed. Results The proportion of pregnant women reporting that vaccines have mild side effects and that are sufficiently tested increased from 78.6 to 92.0% (p = 0.001) and from 79.4 to 93.2% (p = 0.001), respectively. There was a reduction from 33.0 to 23.3% (p = 0.065) in the proportion of those declaring that healthcare workers (HCWs) give information only on the benefits and not on the risks of vaccines, and a reduction from 27.3 to 12.1% (p = 0.001) in those reporting that vaccines are an imposition and not a free choice of mothers. Trust in National Health Service (NHS) operators slightly decreased. Among participants, the monthly flu vaccination adherence ranged from 50.0% in November to 29.2% January for 2019–20 flu season, and from 56.3% in September to 14.5% in January for 2020–21 flu season, showing a higher vaccination acceptance in the earlier months of 2020-21 flu season. Conclusions The pandemic may have positively affected pregnant women's knowledge and opinions about vaccinations and trust in HCWs, despite a possible negative impact on their perceptions about NHS operators. This should inspire Public Health professionals to rethink their role as health communicators.